Thermomechanical Behavior of Late Indo-Chinese Granodiorite under High Temperature and Pressure - Yanjun Zhang; Shuren Hao; Lin Bai; Ziwang Yu; Jianing Zhang; Jingtao Fang (Journal of Engineering)
This study investigates the influence of temperature, effective stress, and rock fracture on the bulk modulus and Biot’s coefficient of granodiorite from a hot dry rock geothermal reservoir using the triaxial compression test. Three types of representative granodiorite samples were chosen for comparative experiments. The experiments were conducted with 0–55 MPa effective stress under cyclic loading. Results show that bulk modulus can continuously increase with the increase in effective stress at a constant temperature. The influencing law on Biot’s coefficient is opposite that on bulk modulus. Interestingly, the temperature effects on the drained bulk modulus and Biot’s coefficient depend on the effective stress. With regard to rock fractures, temperature and effective stress exert similar effects on the Biot’s coefficients and bulk moduli of the samples compared with those of intact rock. The data of this experiment have a wide range of applications because most of the reservoir rocks in dry-hot-rock geothermal system have lithology of granite or granodiorite. The change law of rock modulus and Biot’s coefficient with the temperature and pressure in this experiment provide the data basis for the future simulation calculation making the considered factors more comprehensive and the results closer to the real situation.